Endoscopic Manometric Studies on the Sphincter of Oddi in Patients with Juxtapapillary Duodenal Diverticula - Tomita, Ryouchi; Koshinaga, Shigemichi; Kurosu, Yasuhiko; Tanjoh, Katsuhisa; Abe, Yoshizo (Nippon Shokaki Geka Gakkai zasshi, 1996)
The motor activity of the sphincter of Oddi(SO) was evaluated by endoscopic manometry in 34 subjects, 12 with and 22 without juxtapapillary duodenal diverticula(JPD). In subjects with JPD the SO basal pressure was 12.5±4.9mmHg and the contraction pressure was 100.9±25.4mmHg; in subjects without JPD these values were 19.6±5.0mmHg and 136.6±28.3mmHg, respectively. The differences were statostocally(p<0.01) for basal and contraction pressures. Wave frequency was not significantly different in subjects without JPD(7.3±2.3/min) and with JPD(8.5±1.0/min). The mean percentages of antegrade, simultaneous and retrograde sequences in subjects with JPD were 39.3±11.0%, 17.7± 8.3% and 43.0±11.9%. They were 66.4%±11.0%, 20.0±4.9% and 14.2±9.1%, respectively, in subjects without JPD. The difference was statistically significant(p<0.01) for antegrade and retrograde sequences. The insufficiency of SO in subjects with JPD with JPD could play a major role in the formation of hepatocholangiopancreatic diseases by duodenobillary and duodenopancreatic refluxes.